Which one is more effective for the treatment of rat sepsis model: thalidomide or etanercept? - Ilhan, N.; Susam, S.; Gul, H. F.; Bardas, R.; Ilhan, N. (Comenius Univ, 2017)
OBJECTIVE: We aimed to investigate the protective effect of selected treatment agents on liver injury in lipopolysaccharide (LPS)-induced rat sepsis model. BACKGROUND: The sepsis includes complex inflammatory responses between a microbial pathogen and the host immune system, and leads to organ failure and also death. METHODS: This study was performed with 29 male Wistar Albino rats. Rats were divided randomly into five groups: Sham group, LPS-treated sepsis group, LPS+thalidomide treated group, LPS+etanercept treated group and LPS+thalidomide+etanercept treated group, respectively. Liver tissue tumor necrosis factor alpha (TNF-alpha), interleukin 1 beta (IL-1 beta) and interleukin 6 (IL-6) levels were determined by enzyme-linked immuno-sorbent assay (ELISA) method. The expression of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kappa B) was performed using western blot analysis. RESULTS: The levels of tissue TNF-alpha, IL-1 beta and IL-6 were found statistically significantly higher in sepsis group than in the sham group. TNF-alpha levels were found statistically significantly decreased in LPS+etanercept and LPS+thalidomide+etanercept treated groups when compared with LPS group (p < 0.05). For IL-1 beta and IL-6 levels a statistically significant decline was observed in the LPS+thalidomide and LPS+etanercept treated groups compared to the LPS group (p < 0.05). Expression of NF-kappa B protein in liver tissue was significantly elevated in the LPS group compared to sham group (p < 0.001). In treatment groups, a marked decrease was observed in NF-kappa B protein expression. CONLUSION: The results of this investigation suggested that etanercept and thalidomide administration may have a beneficial effect on LPS-induced sepsis. So, the present study may have significant clinical relevance, but clinical trials are needed to confirm these results (Tab. 1, Fig. 1, Ref. 36). Text in PDF www.elis.sk.
Keywords: sepsis; IL-1 beta; IL-6; TNF-alpha; treatment agents